Interpretative Potential of Abstract and Concrete Common Nouns - E Yu. Pozdnyakova; N. N. Shpilnaya (СибСкрипт)
The article describes the interpretative potential of abstract and concrete common nouns. In interpretational linguistics, any word may become part of dialogue, which means that its semantics is not static. The research objective was to identify differences between abstract and concrete common nouns in interpretational discourse. The linguistic experiment consisted of two stages; its goal was to identify the effect of the word type (abstract / concrete) on its interpretative potential. The respondents were first- and second-year students of the Polzunov Altai State Technical University aged 18–22 y.o. The first stage (109 people) involved modeling the associative field of common nouns while the second one (270 people) featured their use in dialogue speech. The surveys yielded 5,248 associations and 218 dialogues. The interpretative orientation of a word was determined by association, and words that formed an associative chain could be considered as key lexemes used by the recipient to build their own discourse. The semantic components of the associative field of abstract and concrete common nouns generated both synonymous and antonymous reactions. However, the associative field of lexemes with a concrete semantics proved to be more diverse. The analysis of key associates made it possible to identify the referential areas of nouns of abstract and concrete nouns, which were not directly linked to the dictionary lexical meaning as most of them did not correspond with the dictionary definition. Dialogues with abstract nouns seldom included areas associated with their direct (dictionary) definition. Dialogues with concrete nouns hardly involved areas connected with interpretative and figurative meaning.